A new species of Aulacogenia Stål (Hemiptera: Heteroptera: Reduviidae: Stenopodainae) from India - Mukherjee, Paramita; Cai, Wanzhi; Saha, G. K. (Zootaxa, 2015)
A new stenopodaine reduviid, Aulacogenia darjeelingensis sp. nov. belonging to the “corniculata species group” from India is described and illustrated. A key to the Indian species of the genus Aulacogenia Stål is provided.